Virtual states : the Internet and the boundaries of the nation-state - Everard, Jerry, 1956- (London ; New York : Routledge, 2000)
This text analyses the role of the state in a globalising, wired society. The author argues that while information technology poses fundamental challenges to the state, this will mean not the decline but rather the mutation of the state.
pt. 1. Virtual states : theory and practice. W(h)ither the state? -- Internet@www.history.edu -- pt. 2. The developing world. Hungry, thirsty and wired -- Sovereignty, boundary making and the net -- Culture and the other on the internet -- pt. 3. The developed world. Process : the key to the cyborg -- Economy@internet.com -- The @ of war -- pt. 4. Internet and society. Virtually real/really virtual -- Internet censorship : US, Europe and Australia -- Alt.cyberspace.binaries.philosophy.
Includes bibliographical references (pages 162-169) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Information society -- Political aspects; Internet -- Political aspects; Internet -- Social aspects; Nation-state.; Société de l'information -- Aspect politique; Internet -- Aspect politique; Internet -- Aspect social; Nation; nations; COMPUTERS -- Information Technology; Information society -- Political aspects; Internet -- Political aspects; Internet -- Social aspects; Nation-state; Virtuelle Realität; Politik; Gesellschaft; Entwicklungsländer; Internet; Internet; Politieke aspecten; Economische aspecten; Samfundsvidenskab -- Sociologi